Fuzzy programming approach to multi-level programming problems - Sinha, Surabhi (Fuzzy sets and systems, 2003)
Multi-level programming is characterized as mathematical programming to solve decentralized planning problems. We have considered a multi-level linear programming problem and applied fuzzy mathematical programming (FMP) approach to obtain the solution of the system. We have suggested FMP method for the minimization of the objectives using linear membership functions. FMP is a supervised search procedure (supervised by the higher level decision maker (DM)). The higher level DM provides the preferred values of decision variables under his control (to enable the lower level DM to search for his optimum in a wider feasible space) and the bounds of his objective function (to direct the lower level DM to search for his solutions in the right direction).